The Psychology of Creativity in Yusuf Idris’s Travel Experience - boulanar, said (El Omda in Linguistics and Discourse Analysis, 2018)
Researching the dimensions of the journey in Arabic literature is highly important, due to the new values, knowledge, and rich, engaging information it carries. In addition, this literary genre offers a unique reading experience. Therefore, any scholarly approach to this literary phenomenon is considered legitimate, supported by the presence of the necessary conditions found in the travel corpus.